Personality and leadership the short-form revised Eysenck personality questionnaire: A Greek edition (EPQ-RS-GR) - Christine Morfaki (SPOUDAI - Journal of Economics and Business, 2021)
A number of studies have linked personality variables and other stable personal traits to leader effectiveness, giving a solid empirical foundation for the claim that qualities are important in the prediction of leader effectiveness. Instruments for the assessment of the Eysenck's factors of personality, psychoticism (P), extraversion (E), and neuroticism (N), were developed over the course of almost 50 years. The aim of the present study was to evaluate the reliability of the Eysenck Personality Questionnaire-Revised Short Scale (EPQ-RS) in a Greek sample. The EPQ-RS is a 48-self- report questionnaire to assess the dimensions of personality, neuroticism, extraversion, psychoticism, while also including a lie scale. The sample consisted of 332 individuals (166 males, 166 females), undergraduate university students in Business Administration. The findings support the psychometric properties of the extraversion, neuroticism and lie scale. The psychoticism scale, however, was found to be less satisfactory.
Keywords: L20; C18; M12; 330; EPQ-R S; Extraversion; Neuroticism; Psychoticism; PEN model; Leadership